Face-to-face communication (FTFC) and smartphone- mediated communication (SMC) among employees in the public sector - Jayrome, John (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to identify face-to-face communication (FIFC) and smartphone-mediated communication (SMC) among employees' work efficiency in the public sector. In this research, the researcher studied two mediums of communication which are FTFC and SMC. This is a survey research which involves the use of open-ended questionnaire to collect the data. There are six employees interviewed for this study. This research used purposive sampling as the sampling procedure. Open-ended questionnaire were pilot tested using two informants. The collected data were analyzed by using content analysis and thematic analysis. Result from this research reported that there are two new factors of why face to face communication still remains important and three emerging conditions reported of the use of face to face communication. However for smartphone-mediated communication there were features of SMC and three new potentiai of SMC which are teamwork, self-satisfaction and self-development as a result from combining the three potential of SMC reported from past research.